Effect of Ag-Decorated BiVO4 on Photoelectrochemical Water Splitting: An X-ray Absorption Spectroscopic Investigation - Ta Thi Thuy Nga; Yu-Cheng Huang; Jeng-Lung Chen; Chi-Liang Chen; Bi-Hsuan Lin; Ping-Hung Yeh; Chao-Hung Du; Jau-Wern Chiou; Way-Faung Pong; K. Thanigai Arul; Chung-Li Dong; Wu-Ching Chou (Nanomaterials, 2022)
Bismuth vanadate (BiVO4) has attracted substantial attention on account of its usefulness in producing hydrogen by photoelectrochemical (PEC) water splitting. The exploitation of BiVO4 for this purpose is yet limited by severe charge recombination in the bulk of BiVO4, which is caused by the short diffusion length of the photoexcited charge carriers and inefficient charge separation. Enormous effort has been made to improve the photocurrent density and solar-to-hydrogen conversion efficiency of BiVO4. This study demonstrates that modulating the composition of the electrode and the electronic configuration of BiVO4 by decoration with silver nanoparticles (Ag NPs) is effective in not only enhancing the charge carrier concentration but also suppressing charge recombination in the solar water splitting process. Decoration with a small number of Ag NPs significantly enhances the photocurrent density of BiVO4 to an extent that increases with the concentration of the Ag NPs. At 0.5% Ag NPs, the photocurrent density approaches 4.1 mA cm−2 at 1.23 V versus a reversible hydrogen electrode (RHE) under solar simulated light illumination; this value is much higher than the 2.3 mA cm−2 of pure BiVO4 under the same conditions. X-ray absorption spectroscopy (XAS) is utilized to investigate the electronic structure of pure BiVO4 and its modification by decoration with Ag NPs. Analytical results indicate that increased distortion of the VO4 tetrahedra alters the V 3d–O 2p hybridized states. Additionally, as the Ag concentration increases, the oxygen vacancy defects that act as recombination centers in BiVO4 are reduced. In situ XAS, which is conducted under dark and solar illumination conditions, reveals that the significantly enhanced PEC performance is attributable to the synergy of modulated atomic/electronic structures and the localized surface plasmon resonance effect of the Ag nanoparticles.